ASSESSMENT OF HEPATITIS B VIRUS INFECTION STATUS USING A TRIO OF TESTS AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To investigate the prevalence of positive HBsAg test results; (2) To describe hepatitis B virus (HBV) serological profiles using the three-test panel of HBsAg, anti-HBs, and total anti-HBc at Vinmec Times City International General Hospital in 2024.Materials and methods:A cross-sectional descriptive study was conducted on 45,433 serum/plasma samples tested for HBsAg, anti-HBs, and total anti-HBc using the automated immunoassay system Cobas e801 at Vinmec Times City International General Hospital (VMTC) in 2024. Retrospective data on age, sex, and test results of HBsAg, anti-HBs, and total anti-HBc were collected at VMTC.Results:Among 45,433 samples, the prevalence of HBsAg positivity was 5.87%. Males had a significantly higher prevalence (7.32%) than females (4.71%). The lowest prevalence was observed in individuals under 18 years of age (0.43%), while the highest was found in those aged over 46 years (up to 7.53%). Among 30,206 HBsAg-negative, 43.64% lacked protective immunity (anti-HBs
Keywords: Hepatitis B virus, HBsAg, anti-HBs, anti-HBC total, screening